SUCCESSFUL TREATMENT OF MULTIDRUG-RESISTANT ACINETOBACTOR BAUMANII BLISTERS ON THE KNEE - Afridi, Sikandar Aziz; Alvi, Hamid Fazeel; Lodhi, Fahad Saqib; Muhammad, Gul; Qureshi, Zaheer Uddin; Ullah, Raffat; Muhammad, Taj; Afridi, Bakhtiar Ullah (Journal of Ayub Medical College Abbottabad, 2015)
Acinetobacter baumannii (A. baumannii), nosocomial infections, especially those due to multi-drug resistant (MDR) strains, are increasingly detected. This study reports the case of a 50 year old man with blisters on the right knee for 8 months, first admitted through the outpatient department for incisional biopsy. Microbiological and histo-pathological examination confirmed the diagnosis of blisters extending deeply up to the knee joint caused by MDR- A. baumannii. A broad spectrum antibiotic therapy was administered and later readjusted according to the results of microbiological culture and biopsy report. Intensive hemodynamic support was required. An extensive surgical debridement was promptly performed and repeated until complete control of the infection with intravenous colistins. Blisters were excised; wounds were dressed daily with chlorhexidine dressings and polymyxine-impregnated dressing. Wounds were finally covered with split-thickness skin grafts. The infection was overcome 120 days after admission. The graft take was 40%. Postoperative rehabilitation was required because of the functional limitation of lower limb movements at the knee joint. Follow-up at 8 months showed no functional deficit and an acceptable aesthetic result. AB-MDR affecting soft tissues is a life-threatening disease, especially in patients with poor immunity and limited access to health facilities, whose clinical diagnosis may sometimes be challenging. Early recognition and treatment represent the most important factors influencing survival. Keywords: Acinetobacter baumannii, Colistin, Chlorhexidine